Diverse Mechanisms of Resistance against Osimertinib, a Third-Generation EGFR-TKI, in Lung Adenocarcinoma Cells with an EGFR-Activating Mutation - Shigetoshi Nishihara; Toshimitsu Yamaoka; Fumihiro Ishikawa; Tohru Ohmori; Koichi Ando; Sojiro Kusumoto; Yasunari Kishino; Ryo Manabe; Yuki Hasebe; Hironori Sagara; Hitoshi Yoshida; Junji Tsurutani (Cells, 2022)
Osimertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), is used as a first-line treatment for patients with EGFR-mutant non-small cell lung cancer (NSCLC). However, the mechanisms underlying its anticancer activity, particularly the subsequent development of acquired resistance, are unclear. Herein, we investigated the mechanisms underlying the development of osimertinib resistance by treating NSCLC PC-9 cells (harboring an EGFR-activating mutation) with osimertinib, thereby developing five resistant cell lines, i.e., AZDR3, AZDR6, AZDR9, AZDR11, and AZDR14. The amplification of wild-type EGFR in AZDR3 cells and wild-type EGFR and KRAS in AZDR6 cells was also studied. AZDR3 cells showed dependence on EGFR signaling, in addition to afatinib sensitivity. AZDR9 cells harboring KRASG13D showed sensitivity to MEK inhibitors. Furthermore, combination treatment with EGFR and IGF1R inhibitors resulted in attenuated cell proliferation and enhanced apoptosis. In AZDR11 cells, increased Bim expression could not induce apoptosis, but Bid cleavage was found to be essential for the same. A SHP2/T507K mutation was also identified in AZDR14 cells, and, when associated with GAB1, SHP2 could activate ERK1/2, whereas a SHP2 inhibitor, TNO155, disrupted this association, thereby inhibiting GAB1 activation. Thus, diverse osimertinib resistance mechanisms were identified, providing insights for developing novel therapeutic strategies for NSCLC.